Supplementation of Microbial Feed on Performance of Growing Goats - Yadav, C. M.; Meena, N. R.; Meena, N. R. (Indian Journal of Animal Nutrition, 2019)
Thirty growing goats with similar age and body weight were selected from adopted village by krishi vigyan kendra, Bhilwara, Rajasthan and divided into three groups of 10 animals each. One group (T1) as control was maintained on farmer’s practices. While T2 was fed concentrate mixture @1.5% of the body weight and T3 was fed same as in T2 + Microbial feed supplement @ 3g/day/head for 120 days. The average body weight gain /day/head (g) was significantly (P < 0.05) higher in T3 (82.30 ± 0.1) as compared to T2 (74.26 ± 0.14) and T1 (42.00± 0.24) groups. The growth rate of growing goats improved significantly (P < 0.05) higher in microbial feed supplement fed group over control. Hence, it was concluded that feeding of microbial feed supplement along with balance diet improved body weight performance in growing goats.